Between polis and civitas. Eight concepts for understanding the contemporary city - Montestruque Bisso, Octavio (2023)
The article addresses the polis / civitas dichotomy as the origin of the meaning of the city. The relationships of belonging to the place, in this case, determine a series of actions that are guided by both tangible and intangible conditions, that is, they are determined by constructions and people. With this text, we seek to enter into the complexity of thinking about the city today, the contemporary city and its constant growth and sensation of change. For this, eight keys or topics are outlined and allow their understanding, being generic enough so that the reader can translate them and contrast them with their own urban reality.